Perception of Degree Nursing Student’s toward learning outcomes throughout simulation experiences in Nursing Programme at Universiti Sains Malaysia, Kubang Kerian, Kelantan - Asri, Anis Insyirah (Universiti Sains Malaysia, 2015)
Perception like sight and hearing function naturally, these abilities will develop on their own without training, but it is equally true that many aspects of them will improve so much with directed practice that they are considered to be learned skills, knowledge critical thinking and confidence the learning outcomes of simulation experiences. The goal of this descriptive cross-sectional was to assess the perception of degree nursing student’s toward learning outcomes throughout simulation experiences. This study also examined the differences of years of study and perception toward learning outcomes throughout simulation experiences. This studies also to determine the associations between student’s selected social demographic data and learning outcomes of simulation experiences. Self-administered questionnaire was used and the result was analysed using one-way ANOVA and independent T test to test the hypotheses in this study. The result shows the significant mean difference of years of study and self learning outcomes at the p < 0.05 level for the three condition [F 6.377 (2.00), p = 0.000]. Post hoc comparisons using the Tukey HSD test indicated that the mean score for the year one (M = 4.88, SD - 0.40) was significantly different than the year two (M = 4.41, SD = 0.80). However, the year one (M = 4.88, SD = 0.40) was significantly difference than year three (M = 4.29, SD = 0.99) that mean score and standard deviation of social domain 15.21 (2.20) was slightly higher than the other domains, physical was 14.71 (2.19), psychological was 15.06 (2.10) and environment was 14.33 (2.09). The null hypothesis was rejected and the finding was significant. As conclusion, many degree nursing students has good perception towards learning outcomes throughout simulation experiences.